Calix[4]arene-based fluorescent probe and the adsorption capacity of its electrospun nanofibrous film for the cesium cation as an adsorbent. Issue 2 (1st February 2017) - Jung, Sung Ho; Park, Jeong Su; Choi, Yeonweon; Kim, Sung Kuk; Jung, Jong Hwa
Abstract: Calix[4]arene-based cation receptor 1 has been synthesised by following a multi-step synthetic procedure. The fluorescence properties of 1 upon the addition of various metal ions were investigated by fluorescence spectroscopy. As a result, it was revealed that 1 displayed dramatic quenching effect upon the exposure to Cs + . In contrast, no significant quenching effects were observed upon the addition of other metal ions such as Li +, Na +, K +, Mg 2+, Ca 2+, Sr 2+, Ag +, Zn 2+ and Ni 2+ . Compound 1 was also found by Job plot to form a 1:1 complex with Cs + . In addition, we also prepared 1-embedded electrospun nanofibrous film (NF-1) as an adsorbent for Cs + . NF-1 is proved to adsorb Cs + effectively from an aqueous solution, indicating that it would be usefully utilised as an adsorbent to remove Cs + . Abstract :